Фазові перетворення в деяких аліфатичних молекулярних кристалах в умовах обмеженого простору - Lazarenko, M. M.; Alekseev, A. N.; Alekseev, S. A.; Grabovsky, Yu. E.; Lazarenko, M. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
Phase transformations of nanostructured 1-octadecene and 10-undecylenic acid were studied by thermophysical methods, FTIR spectroscopy and X-ray diffraction. It was shown that bulk as well as nanostructured 1-octadecene crystallizes in orthorhombic unit cell. However, the unit cells of 10-undecylenic acid in bulk and inside the porous silicon are differen, but with the same large period of the pattern. The transition between orthorhombic crystalline and orthorhombic rotation-crystalline phases in boundary layer takes place at -60oC for nanostructured 1?octadecene and at -95oC for nanostructured 10-undecylenic acid. At the same time, the melting temperatures decrease in the confined media comparing to bulk for both substances (?Т = 11°C and ?Т = 19°C, respectively).